Aspectos reprodutivos, morfologia dos gametas e desenvolvimento embrionário de Astyanax altiparanae Garutti & Britski (Teleostei, Characidae) - Santos, Matheus Pereira dos [UNESP] (2014)
The aim of this study was to study basic aspects of gametes and early development of yellowtail tetra Astyanax altiparanae, for future application in biotechnology including chromosome and embryo manipulation. In Chapter I, the oocytes were analyzed by Scanning Electron Microscopy (SEM) and the insemination dose was determined. Semen was also collected and analyzed using a Computer Assisted Sperm Analysis (CASA). Such a reduced inseminating dose was explained by oocyte morphology because SEM analysis revealed villosities surrounding the micropyle that is related to the sperm guidance for fertilization. In addition, the duration of sperm motility was longer in comparison to most teleosts, what may improve fertilization ability. In Chapter II, several parameters related with fertilization were described, including the second polar body extrusion, fusion of the pronuclei and the formation of the fertilization cone. Moreover, the effect of three temperatures (22°C, 26°C and 30°C) on developmental stages was determined. 2nd polar body was extruded at 4-6 minutes post fertilization (mpf), and the pronuclei were formed at 8-10 mpf. The sperm showed a spherical head, midpiece and flagellum. As expected, higher temperatures gave rise to faster development and hatching. The information obtained in this study will open new possibilities in the field of chromosome and embryo manipulation including poliploidy, chimerism, transgenesis and other techniques